2002
DOI: 10.1080/000155502320624069
|View full text |Cite
|
Sign up to set email alerts
|

Palmoplantar Pustulosis: an Autoimmune Disease Precipitated by Smoking?

Abstract: Ninety-five percent of patients with palmoplantar pustulosis are smokers at onset of the disease. The aim of this study was to determine whether these patients have serum antibodies to nicotinic acetylcholine receptors (nAChR ab) and if their sera induce a specific immunofluorescence in normal palmar skin. Sera from 45 patients with palmoplantar pustulosis and 23 patients with chronic hand eczema were analysed for muscle nAChR ab, and immunofluorescence was performed on healthy palmar skin. Forty-two percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 3 publications
6
39
1
3
Order By: Relevance
“…Occupational physicians can play an active role in smoking prevention and cessation and must provide their smoking employees incentive, guidance and intervention to help them discontinue this habit. Tobacco smoking is known to influence various inflammatory skin diseases [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. An association between smoking and HE has been postulated [16,19,22,23,24,25,26] and the present findings underscore that smoking has a negative impact on work-related HE.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Occupational physicians can play an active role in smoking prevention and cessation and must provide their smoking employees incentive, guidance and intervention to help them discontinue this habit. Tobacco smoking is known to influence various inflammatory skin diseases [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. An association between smoking and HE has been postulated [16,19,22,23,24,25,26] and the present findings underscore that smoking has a negative impact on work-related HE.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to its well-known long-term complications, smoking is also known to influence various inflammatory skin diseases. Thus, smoking has been shown to be a risk factor for developing lupus erythematodes [10,11,12], palmoplantar pustulosis [13,14,15] and, to some extent, also psoriasis [16,17]. Numerous studies have linked cigarette smoking with delayed wound healing and a number of wound-related complications [18].…”
Section: Introductionmentioning
confidence: 99%
“…21 Ten patients (43%) with eczematiform lesions and 28 patients (45%) with psoriasiform lesions were smokers. Palmoplantar lesions, which can be triggered by smoking, 22 were observed in 22 patients of whom 15 (68%) were smokers. This close relationship has also been observed for other forms of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fibroblast migration into lesional skin is inhibited (13,14). Smoking has been suspected to be a risk factor for skin diseases such as lupus erythematosus (15,16), palmoplantar pustulosis (17,18), psoriasis (19,20), and hidradentis suppurativa (21). In two of these diseases, hidradentis suppurativa and palmoplantar pustulosis, the data have indicated that the cessation of smoking may improve the disease (22,23).…”
mentioning
confidence: 99%